2015
DOI: 10.1038/ncomms8798
|View full text |Cite
|
Sign up to set email alerts
|

Understanding complete oxidation of methane on spinel oxides at a molecular level

Abstract: It is crucial to develop a catalyst made of earth-abundant elements highly active for a complete oxidation of methane at a relatively low temperature. NiCo 2 O 4 consisting of earth-abundant elements which can completely oxidize methane in the temperature range of 350-550°C. Being a cost-effective catalyst, NiCo 2 O 4 exhibits activity higher than precious-metal-based catalysts. Here we report that the higher catalytic activity at the relatively low temperature results from the integration of nickel cations, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
212
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(225 citation statements)
references
References 47 publications
11
212
1
1
Order By: Relevance
“…In situ studies of surface chemistry of these catalysts were performed on the ambient pressure XPS using monochromated Al Ka in the Tao group 11,29,30 . The binding energy of catalyst samples were calibrated to Au 4f 7/2 at 84.0 eV and Ag 3d 5/2 at 368.3 eV (ref.…”
Section: Methodsmentioning
confidence: 99%
“…In situ studies of surface chemistry of these catalysts were performed on the ambient pressure XPS using monochromated Al Ka in the Tao group 11,29,30 . The binding energy of catalyst samples were calibrated to Au 4f 7/2 at 84.0 eV and Ag 3d 5/2 at 368.3 eV (ref.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a recent study has shown that NCO can completely oxidize methane to CO 2 and water in the temperature range of 350-550 C 7 . Considering that NCO is also a cheap material made of earth-abundant elements, this result suggests that NCO may be a better methane oxidation catalyst than typical precious-metal-based catalysts 8 .…”
Section: Introductionmentioning
confidence: 99%
“…various bulk 13,19 and surface 7,20 properties have been investigated, but many aspects of the behavior of this material, e.g. the origin of the half-metallic ferrimagnetic structure and the influence of oxygen vacancies, are still largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer this question, we examined the CO adsorption energies on the one-atom substituted Pt alloy surfaces. This system was chosen due to the following reasons: Firstly, the adsorption of CO is very important in many reactions such as CO oxidation 37,40 , dry reforming 38 , CO 2 reduction 41 , and methane oxidation 42 . Secondly, CO adsorbs on the top site of Pt(111), which can also test the generality of the BCCF.…”
Section: Resultsmentioning
confidence: 99%